THE SITUATION OF REFERENCE HOSPITALS FOR THE ESTABLISHMENT AND OPERATION OF PATIENT SAFETY CENTERS - Juliana do Nascimento Serra; Ana Rita Barbieri; Maria de Fátima Meinberg Cheade (Universidade Federal do Paraná, 2016)
This study was conducted to learn how reference hospitals employ guidelines and protocols on patient safety in relation to the instatement of the corresponding national policy. A descriptive study with a quantitative approach was conducted in the six reference hospitals of the state of Mato Grosso do Sul in 2014, witha script developed using the normative framework of National Policy for Patient Safety resolutions of theHealth Surveillance and recommendations of World Health Organization. Findings show that even within Patient Safety Centers, protocols such as surgical prophylaxis, surgical safety checklists and adverse event reporting are observed. Some hospitals lack structure, which prevent full adherence to protocols. This fact is compounded by the shortages of workers, equipment and resources. Results show that the existence of resolutions and guidelines are not enough to guarantee patient safety.